(untitled) (Global Business Management Review (GBMR), 2022)
The exchange rate volatility and its modelling has gained importance since the breakdown of Bretton Woods System in 1973 and subsequent movement of many countries shifting from fixed exchange rate system to floating exchange rate system. India shifted from fixed exchange rate to the Liberalized Exchange Rate Management System (LERMS) in 1992 and market determinant exchange rate regime in 1993 which is a major structural changes in Indian foreign exchange market. This has lead to huge volatility in exchange rate. Exchange rate volatility induces uncertainty in international transactions. This uncertainty reduces international trade and the growth of the economy. The present study is an attempt to analyse the volatility and uncertainty of exchange rate with specific reference to INR vs MYR (Malaysian Ringgit) based on the past 14 years daily exchange rate while the time series properties of the data was examined using the ADF and PP approach, the stationary process, and order of the incorporated series. The ARCH and GARCH models were used to examine the degree or severity of volatility based on the first difference estimated volatility. AR GARCH results showed that lagged (last year) exchange rate is significantly responsible for the dynamics of INR vs MYR exchange rate in India. Further, the Granger causality test conducted shows that the direction of causality is more powerful and significant from actual exchange rate to exchange rate uncertainty in India.